Fast atom diffraction for grazing scattering of Ne atoms from a LiF(0 0 1) surface - Gravielle, Maria Silvia (2011)
Angular distributions of fast Ne atoms after grazing collisions with a LiF(0 0 1) surface under axial surface channeling conditions are experimentally and theoretically studied. We use the surface eikonal approximation to describe the quantum interference of scattered projectiles, while the atom–surface interaction is represented by means of a pairwise additive potential, including the polarization of the projectile atom. Experimental data serve as a benchmark to investigate the performance of the proposed potential model, analyzing the role played by the projectile polarization.